Phytochemical analysis of Passiflora loefgrenii Vitta, a rich source of luteolin-derived flavonoids with antioxidant properties. (5th August 2015) - Argentieri, Maria Pia; Levi, Marisa; Guzzo, Flavia; Avato, Pinarosa
Abstract: Objectives: The paper describes the flavonoid composition of the aerial parts (young leaves, YL; adult leaves, AL; stems, ST) of Passiflora loefgrenii Vitta, a rare species native to Brazil, where it is traditionally used as food. Antioxidant potential has also been evaluated. To the best of our knowledge, no phytochemical and biological study on this species has been reported previously. Methods: Compositional data have been acquired combining HPLC-diode array detector (DAD) and Electrospary ionization-tandem mass spectrometry (ESI-MS/MS) analyses. Antioxidant activity has been evaluated by the 2, 2′-di-phenyl-1-picrylhydrazyl method. Key findings: Glycosylated flavones, with luteolin as the main aglycone, can be regarded as biomarkers for this drug. Qualitative composition of the extracts from YL, AL and ST was similar. The bulk of the constituents was made up by 8- C -ß-glucosyl luteolin (orientin), 7 -O -α-rhamnosyl-6- C -ß-glucosyl luteolin and 6- C -α-rhamnosyl luteolin, which totally amounted to 16.57 (73%), 10.77 (74%) and 5.07 (77%) μg/mg in YL, AL and ST, respectively. P. loefgrenii showed a good antioxidant activity (IC50 of 350 μg/ml), higher than generally reported for other passifloras. Conclusions: P. loefgrenii, rich in luteolin glycosides, can be regarded as a good candidate to be explored for therapeutic properties other than the sedative one since it represents a rich source of valuable flavonoids with antioxidant potential.